Praravinia neriifolia - Hoo, P.K.; Colin Ruzelion Maycock; Damit, A.; Khoo, E.; Nilus, R.; Sugau, J.; Tanggaraju, S.; Tsen, S.; Pereira, J.T. (International Union for Conservation of Nature and Natural Resources, 2020)
Praravinia neriifolia was recorded only once from the Payao River, Sandakan in 1928 and no subsequent collection has been made. The estimated area of occupancy (AOO) and extent of occurrence (EOO) are both 4 km2. Based on satellite image of the Payao River, most of the lowland forests has been cleared for palm oil plantations, indicating severe habitat loss. Surveys are needed with the intention of producing more collections from the Payao River area to ascertain its current geographic range and whether the species is still extant. Until then, it is assessed as Critically Endangered (Possibly Extinct). Praravinia neriifolia is endemic to Sabah, Malaysia. It was recorded only from Payao River, Sandakan. The species has not been collected since 1928, surveys are needed to confirm any current remaining localities of the species.